Placement of lumboperitoneal shunt: Etiology of iatrogenic gastric perforation - Guzelyuz, Betul; Taşkın, Halit Eren; Kemerdere, Rahşan; Kösem, Yağmur Özge Turaç; Tahmazoğlu, Burak; Çetintaş, Semih Can (Journal of Surgery and Medicine, 2022)
Iatrogenic perforation can cause gastric perforation; among the complications of lumboperitoneal shunt placement, intestinal perforation is extremely rare vs. infectious complications; perforation may occur in the ascending colon with projection of the incision site. This case involves a 41-year-old patient, with gastric perforation from pseudotumor cerebri during incision in the abdominal right quadrant to insert a lumboperitoneal shunt.